The performance evaluation of link-sharing method of buffer in NoC router - Fukase, Naohisa; Miura, Yasuyuki; Watanabe, Shigeyoshi; Rahman, M.M. Hafizur (2013)
We have proposed a memory sharing method of the wormhole routed network-on-chip architecture. In our method, a memory is shared between multiple physical links by using the multi-port memory. We evaluate and discuss the communication performance in the various situations. It is shown that the required number of memory banks required in multiport memory for 2D-torus and 2D-mesh networks is 8. Our proposed method yields high performance for both torus and mesh networks. Even this high performance is retained when the buffer size and the packet length are same.